Anxiety among students during the pandemic - Results from the C-19 German Student Well-being Study: Eileen Heumann. (25th October 2022) - Heumann, E; Helmer, SM; Busse, H; Negash, S; Pischke, CR; Trümmler, J; Niephaus, Y; Stock, C
Abstract: Background: Anxiety is widespread among university students. The COVID-19 pandemic af-fected students' mental health negatively. Given the long duration of the pandemic monitoring mental health remains important. This study aims to determine to which extent anxiety is preva-lent among students (1), what factors are associated with it (2) and which student groups are mostly affected (3). Methods: The cross-sectional COVID-19 German Student Well-being Study (C19 GSWS) sur-veyed mental health and well-being of students at five universities in Germany from 27.10.-14.11.21. Anxiety was assessed using the GAD-2. Associations between anxiety and sociodem-ographic, socioeconomic/social support factors as well as health- and COVID-19-related factors were determined using multiple binary logistic regression models. Results: The mean age of students was 24.1 years (SD = 4.9), 67% were women and 31% men. The prevalence of anxiety was 32% and diverse gender (OR = 3.98, 95% CI: 1.71-9.23), a com-plicated relationship status (OR = 1.66, 95% CI: 1.06-2.60), the lack of a confidant (OR = 2.50, 95% CI: 1.80-3.46), and financial difficulties (e.g., being able to cover monthly expenses; OR = 1.76, 95% CI: 1.36-2.29) were associated with anxiety. Participants who were worried about (re)infection with COVID-19 had a 1.28-times higher chance (OR, 95% CI: 1.03-1.59) for anxie-ty. Students who were (rather) not worried that a relative would become severely ill with COVID-19 had a lower chance to experience anxiety (OR = 0.72, 95% CI: 0.53-0.98) as well as those who were confident receiving medical care in case of an infection with COVID-19 (OR = 0.80, 95% CI: 0.65-0.98). Conclusions: Concepts for prevention and counselling in terms of mental health problems in students should be developed considering specific stressors due to the pandemic. Key messages:  This study shows that anxiety is widespread among university students and associated with a variety of stressors.  The findings can help to develop specific concepts for prevention and counselling.